Circulating tumor cells exhibit stem cell characteristics in an orthotopic mouse model of colorectal cancer - Schölch, Sebastian; García, Sebastián A.; Iwata, Naoki; Niemietz, Thomas; Betzler, Alexander M.; Nanduri, Lahiri K.; Bork, Ulrich; Kahlert, Christoph; Thepkaysone, May-Linn; Swiersy, Anka; Büchler, Markus W.; Reißfelder, Christoph; et al. (OncoTarget, 2016)
The prognosis of colorectal cancer (CRC) is closely linked to the occurrence of distant metastases, which putatively develop from circulating tumor cells (CTCs) shed into circulation by the tumor. As far more CTCs are shed than eventually metastases develop, only a small subfraction of CTCs harbor full tumorigenic potential. The aim of this study was to further characterize CRC-derived CTCs to eventually identify the clinically relevant subfraction of CTCs.
Gesehen am 20.05.2020